Manual de funciones para el departamento de administración de un hotel. - Sanchez Jaramillo, Janeth Elizabeth (My University, 2018)
Tourism is an activity that boosts the economy of the people, in this sense it is a source of employment both direct and indirect, as well as it is able to improve the quality of life of the inhabitants who are involved. Among the companies that stand out most in the tourist field are the hotels or lodging, which have undergone an enormous development and innovation, adapting to the changes generated by the environment and the search for the satisfaction of the guests. The present work consists in the elaboration of a manual of activities for the administrative area of a hotel, detailing the daily tasks and performing them in an efficient way, fulfilling the expectations of the client and ensuring the quality of the company. In addition, this document allows to know the internal functioning of the department, since it describes the tasks, involved and responsible for its execution. Many hotels have been created without a clear organizational structure and consistent with the type of services offered, and, above all, with a lack of manuals that indicate the correct way to execute the established activities. It is important to bear in mind that all the activities carried out in the Administration department are aimed at achieving the company's objectives and with it the economic benefits, without neglecting the most important element "the guest".
El turismo es una actividad que dinamiza la economía de los pueblos, en este sentido es fuente generadora de empleos tanto directos como indirectos, así mismo es capaz de mejorar la calidad de vida de los habitantes que están involucrados. Entre las empresas que más se destacan en el campo turístico están las hoteleras o de alojamiento, que han experimentado un enorme desarrollo e innovación, adaptándose a los cambios que generan el entorno y la búsqueda de la satisfacción de los huéspedes. El presente trabajo consiste en la elaboración de un manual de actividades para el área administrativa de un hotel, detallando las labores diarias y realizarlas de una manera eficiente, cumpliendo con las expectativas del cliente y asegurando la calidad de la empresa. Además, este documento, permite conocer el funcionamiento interno del departamento, puesto que describe las tareas, involucrados y responsables de su ejecución. Muchos hoteles han sido creados sin una estructura organizativa clara y coherente al tipo de servicios que ofrece, y, sobre todo, con falta de manuales que indiquen la manera correcta de ejecutar las actividades establecidas. Es importante tener en cuenta que todas las actividades realizadas en el departamento de Administración están encaminadas a conseguir los objetivos de la empresa y con ello los beneficios económicos, sin dejar de lado al elemento más importante “el huésped”.
Keywords: HOTELES; MANUAL; FUNCIONES; CALIDAD